2022
DOI: 10.1108/jpbm-01-2022-3830
|View full text |Cite
|
Sign up to set email alerts
|

Brand equity and stock performance in time of crisis: evidence from the COVID-19 pandemic

Abstract: Purpose This paper aims to investigate the impact of brand equity (BE) on stock performance (i.e. stock return, volatility and beta), and compare the performance of a high brand equity stocks (HBES) portfolio with that of the overall market during market downturn, market upturn and total disturbance periods of the COVID-19 pandemic in 2020. Design/methodology/approach Stock performance data and brand valuation estimates are obtained from various sources to assemble a portfolio of HBES and conduct the analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 75 publications
(195 reference statements)
4
12
0
Order By: Relevance
“…As a global crisis, COVID-19 serves as a crucial example of understanding how brands can effectively engage consumers during crisis contexts and offers insights applicable to other crises. A recent study showcased the positive influence of brand equity on stock performance during the pandemic, underscoring the proactive role of branding in times of crisis (Farhang et al, 2023). It was also found that crisis-related brand messages were more effective for consumers with lower social connection during the pandemic (Garcia-Collart, 2023).…”
Section: Brand Communications During a Global Crisismentioning
confidence: 96%
“…As a global crisis, COVID-19 serves as a crucial example of understanding how brands can effectively engage consumers during crisis contexts and offers insights applicable to other crises. A recent study showcased the positive influence of brand equity on stock performance during the pandemic, underscoring the proactive role of branding in times of crisis (Farhang et al, 2023). It was also found that crisis-related brand messages were more effective for consumers with lower social connection during the pandemic (Garcia-Collart, 2023).…”
Section: Brand Communications During a Global Crisismentioning
confidence: 96%
“…Many researchers have already studied the relationship between brand equity and financial performance, by using rankings of valuable brands, such as Billet et al (2014), Fehle et al (2008, Johansson et al (2012), Madden et al (2006), Voss and Mohan (2016), Oliveira et al (2018) and Farhang et al (2023), who conducted surveys to compare the financial performance of a portfolio composed of companies classified as most valuable brands with a market portfolio of other companies listed on the stock exchange. In general, these studies have shown that a portfolio of companies that develop valuable brands presents higher returns than market portfolios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2006), Voss and Mohan (2016), Oliveira et al. (2018) and Farhang et al. (2023), who conducted surveys to compare the financial performance of a portfolio composed of companies classified as most valuable brands with a market portfolio of other companies listed on the stock exchange.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The chosen theory relates to this study because brand equity is an intangible resource that can improve a company's competitive advantage (Chaudhry and Ramakrishnan, 2019). Other past and recent studies that also incorporated this theory are found the work of Balis (2020), Cooper et al (2023), Farhang et al (2023) and He and Estebanez (2023).…”
Section: Introductionmentioning
confidence: 99%